ANALISIS YURIDIS PELAKSANAAN PENETAPAN GANTI RUGI ATAS TANAH AKIBAT PELEBARAN JALAN DI DAERAH DESA SUMBER MUFAKAT (Studi Atas Pelebaran Jalan Di Desa Sumber Mufakat, Kecamatan Kabanjahe, Kabupaten Karo) - RIZKY FAUZI SEMBIRING (Ilmu Hukum Prima (IHP), 2020)
One’s land does not only function for its owner, but also for all Indonesian people in general. Consequently, the land use is not only oriented to the land title holder’s benefit, but it also has to notice and consider the sake of society, in order to implement balance of interests principle. The research problems are how the implementation of indemnity for the land used for village development in Sumber Mufakat Village is in line with the Regulations of the President of the republic of Indonesia Number 148/2015 on the Fourth Amendment to the Regulation of the President Number 71/2012 on Implementation of Land Procurement for Development of Public Interest; what factors impede the implementation of indemnity stipulated for village development in Sumber Mufakat Village, and about the legal efforts made related to the problems in indemnity for the land used for village development in Sumber Mufakat Village. This is a normative juridical research with descriptive analysis. The data used in this research consist of secondary data. They are collected through library study and field research. Qualitative analysis is employed of the data analysis. There are some types and forms of indemnity stipulated in the law such as Article 74 of the Regulation of the president Number 71/2012 on Land procurement for the development of public interest by Government or Regional Government. The obstacles are encountered in determining the form and amount of indemnity for road widening in Sumber Mufakat Village which come in variety. The object of land procurement is being disputed in the court, the indemnity is taken by the rightful party in the secretariat of the Court after there is a court ruling with permanent legal enforcement or a deed of reconciliation, and a covering letter from the Head of Land Procurement Execution (Regional Office of National Land Office in Province of Head of Land office in Regency/District). It is suggested that Government notice the interest of land title’s holder in the road widening at Sumber Mufakat Village. In addition, it is necessary to make approaches and provide opportunities to land title owner to choose which type and form of indemnity is preferred for the road widening in Sumber Mufakat Village. It is recommended that every institution implement the law in line with the prevailing regulation impartially. It is expected that every institution to not take side to any particular government institution with higher position. It is also advised that the court implement legal regulations to achieve legal purpose, namely justice, certainty and usefulness.